Zaprzedać duszę diabłu – reprodukowalność mitu we frazematyce z polskiego obszaru gwarowego i języka potocznego w kontekście kultury tradycyjnej - Ewa Masłowska (Ksiegarnia Akademicka Publishing, 2021)
Selling One’s Soul to the Devil – Reproducibility of the Mythical Motif in Phrasematics of the Polish Colloquial Language in the Context of Traditional Culture